2011
DOI: 10.1029/2010gl046566
|View full text |Cite
|
Sign up to set email alerts
|

A case study of an elevated stratopause generated in the Whole Atmosphere Community Climate Model

Abstract: The Whole Atmosphere Community Climate Model (WACCM) is used to study the influence of gravity waves on the generation and evolution of an elevated stratopause following a sudden stratospheric warming (SSW). By comparing WACCM simulations of two Arctic winters, where one is dynamically undisturbed and one is disturbed, we find that intense planetary wave activity during a SSW drives the reversal of the zonal mean wind in the stratosphere. This alters the penetration of eastward propagating, non‐orographic grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 17 publications
3
78
0
Order By: Relevance
“…Various modelling studies have shown eastward GW forcing anomalies at mesosphere and lower thermosphere (MLT) altitudes in relation to SSWs (e.g. Yamashita et al, 2010;Chandran et al, 2011Limpasuvan et al, 2012), a result that has been confirmed by radar observations of GW forcing at mesopause heights during the 2013 major SSW (de Wit et al, 2014b). Model studies have shown this departure away from climatological wintertime westward GW forcing to be associated with the weakening or reversal of the wintertime residual circulation and associated cooling of the mesosphere during…”
Section: Introductionmentioning
confidence: 80%
“…Various modelling studies have shown eastward GW forcing anomalies at mesosphere and lower thermosphere (MLT) altitudes in relation to SSWs (e.g. Yamashita et al, 2010;Chandran et al, 2011Limpasuvan et al, 2012), a result that has been confirmed by radar observations of GW forcing at mesopause heights during the 2013 major SSW (de Wit et al, 2014b). Model studies have shown this departure away from climatological wintertime westward GW forcing to be associated with the weakening or reversal of the wintertime residual circulation and associated cooling of the mesosphere during…”
Section: Introductionmentioning
confidence: 80%
“…A striking aspect of the unusual dynamics of those winters were shown in the observations of temperature (Manney et al 2005(Manney et al , 2008(Manney et al , 2009Orsolini et al 2010) and simulations of similar events by WACCM (Chandran et al 2011;Limpasuvan et al 2011). In those winters, the position of the stratopause, identified as the middle atmosphere temperature maximum, jumped from its average altitude range (45-55 km) to 75-85 km.…”
Section: Mlt Variations Due To Active Winter Dynamicsmentioning
confidence: 89%
“…For example, model simulations show that the formation of the new stratopause is sensitive to nonorographic gravity wave drag (e.g., Chandran et al, 2011;Ren et al, 2011). Further, model simulations that explicitly resolve a considerable part of the gravity wave spectrum reveal that during PJO events the dissipation altitude of westward propagating gravity waves is higher after the SSW than before.…”
Section: Effects Of Gravity Waves During Sswsmentioning
confidence: 99%